Efficacy and safety of Tripterygium wilfordii Hook F preparations for the treatment of Crohn disease: A systemic review and meta-analysis protocol - Zhang, Jianying (Medicine (Baltimore), 2019)
BACKGROUND: Crohn disease (CD) is associated with substantial healthcare related costs and impairment of quality of life. Tripterygium wilfordii Hook F (TwHF) is proved to be effective for CD in animal and human. However, there is no systemic review and meta-analysis regarding the clinical efficacy and safety of TwHF preparation for the treatment of CD. METHODS: Six electronic databases (Medline, EMBASE, Cochrane database, Chinese National Knowledge Infrastructure, Wanfang Database and Chongqing VIP Database) will be searched for eligibility studies. Data from the included studies will be extracted and the quality of studies will be assessed. Data synthesis will be performed using Review Manager software. Sensitivity analysis and publication bias assessment will also be carried out. RESULTS: This systemic review and meta-analysis will provide synthesized result of clinical efficacy and safety of TwHF preparation for the treatment of CD. CONCLUSION: This research will determine the clinical efficacy and safety of TwHF preparation for the treatment of CD. Registration: PROSPERO CRD42019127893